Reversing Epigenetic Gene Silencing to Overcome Immune Evasion in CNS Malignancies - Ratnam, Nivedita M.; Sonnemann, Heather M.; Frederico, Stephen C.; Chen, Huanwen; Hutchinson, Marsha-Kay N. D.; Dowdy, Tyrone; Reid, Caitlin M.; Jung, Jinkyu; Zhang, Wei; Song, Hua; Zhang, Meili; Davis, Dionne; et al. (Frontiers in Oncology, 2021)
Glioblastoma (GBM) is an aggressive brain malignancy with a dismal prognosis. With emerging evidence to disprove brain-immune privilege, there has been much interest in examining immunotherapy strategies to treat central nervous system (CNS) cancers. Unfortunately, the limited success of clinical studies investigating immunotherapy regimens, has led to questions about the suitability of immunotherapy for these cancers. Inadequate inherent populations of tumor infiltrating lymphocytes (TILs) and limited trafficking of systemic, circulating T cells into the CNS likely contribute to the poor response to immunotherapy. This paucity of TILs is in concert with the finding of epigenetic silencing of genes that promote immune cell movement (chemotaxis) to the tumor. In this study we evaluated the ability of GSK126, a blood-brain barrier (BBB) permeable small molecule inhibitor of EZH2, to reverse GBM immune evasion by epigenetic suppression of T cell chemotaxis. We also evaluated the in vivo efficacy of this drug in combination with anti-PD-1 treatment on tumor growth, survival and T cell infiltration in syngeneic mouse models. GSK126 reversed H3K27me3 in murine and human GBM cell lines. When combined with anti-PD-1 treatment, a significant increase in activated T cell infiltration into the tumor was observed. This resulted in decreased tumor growth and enhanced survival both in sub-cutaneous and intracranial tumors of immunocompetent, syngeneic murine models of GBM. Additionally, a significant increase in CXCR3+ T cells was also seen in the draining lymph nodes, suggesting their readiness to migrate to the tumor. Closer examination of the mechanism of action of GSK126 revealed its ability to promote the expression of IFN-g driven chemokines CXCL9 and CXCL10 from the tumor cells, that work to traffic T cells without directly affecting T maturation and/or proliferation. The loss of survival benefit either with single agent or combination in immunocompromised SCID mice, suggest that the therapeutic efficacy of GSK126 in GBM is primarily driven by lymphocytes. Taken together, our data suggests that in glioblastoma, epigenetic modulation using GSK126 could improve current immunotherapy strategies by reversing the epigenetic changes that enable immune cell evasion leading to enhanced immune cell trafficking to the tumor.